Concentration dynamics of coarse and fine particulate matter at and around signalised traffic intersections. Issue 9 (25th August 2016) - Kumar, Prashant; Goel, Anju
Abstract : The understanding of rapidly evolving concentrations of particulate matter (PMC) at signalised traffic intersections (TIs) is limited, but it is important for accurate exposure assessment. Abstract : The understanding of rapidly evolving concentrations of particulate matter (PMC) at signalised traffic intersections (TIs) is limited, but it is important for accurate exposure assessment. We performed "mobile" and "fixed-site" monitoring of size-resolved PMCs in the 0.25–34 μm range at TIs. On-road mobile measurements were made inside a car under five different ventilation settings on a 6 km long round route, passing through 10 different TIs. Fixed-site measurements were conducted at two types (3- and 4-way) of TIs. The aims were to assess the effects of different ventilation settings on in-vehicle PMCs and their comparison during delay conditions at the TIs with those experienced by pedestrians while crossing these TIs. We also estimated the zone of influence (ZoI) for PM10, PM2.5 and PM1 under different driving conditions and fitted the probability distribution functions to fixed-site data to understand the concentration and exposure dynamics of coarse and fine particles around the studied (3- and 4-way) TIs. The fine particles (PM2.5 ) showed a strong positive exponential correlation with the air exchange rates under different ventilation settings compared with coarse particles (PM2.5–10 ) showing an opposite trend. This suggested that the ventilation system of the car was relatively more efficient in removing coarse particles from the incoming outside air. On-road median PM10, PM2.5 and PM1 during delays at the TIs were ∼40%, 16% and 17% higher, respectively, compared with free-flow conditions on the rest of the route. About 7% of the average commuting time spent during delay conditions over all the runs at the TIs corresponded to 10, 7 and 8% of the total respiratory deposition dose (RDD) for PM10, PM2.5 and PM1, respectively. The maximum length of the ZoI for PM2.5 and PM1 was highest at the 4-way TI and the maximum length of the ZoI for PM10 was highest at the 3-way TI. The on-road average RDD rate of PM10 inside the cabin when windows were fully open was up to ∼7-times that for pedestrians at the TIs.